Factors Associated With Diagnostic Delays in Human Brucellosis in Tongliao City, Inner Mongolia Autonomous Region, China - Zhai, Jingbo; Peng, Ruihao; Wang, Ying; Lu, Yuying; Yi, Huaimin; Liu, Jinling; Lu, Jiahai; Chen, Zeliang (Frontiers in Public Health, 2021)
The time delay in diagnosis poses a huge challenge to human brucellosis, which increase the risk of chronicity, complications and accordingly aggrandize economic burden of the patients. Identification of risk factors in diagnostic delay is the key for its prevention or reduction. With data collected from Tongliao City, Inner Mongolia Autonomous Region of China, risk factors associated with diagnostic delay were analyzed. Diagnostic delay was defined with cutoff of 30, 60 and 90 days. Risk factors of diagnostic delay in different delay groups were analyzed by univariate analysis and modelled by multivariate logistic regression analysis. A total of 14,506 cases were collected between January 1, 2005 and December 31, 2017, of which the median diagnostic delays was 29 days (interquartile [IQR] range: 14–54 days). Logistic regression analysis indicated that older age was associated with longer diagnostic delay across all groups. Longer diagnostic delay with increasing of age among three delay groups (P for trend<0.001). Occupation as herdsman was associated with shorter diagnostic delay in the group-1 with 30 days(aOR, 0.890 [95% CI 0.804-0.986]). Diagnostic delay was significantly shorter in brucellosis patients who reported in CDC at different delay groups (aOR 0.738 [95% CI 0.690-0.790], 0.539 [95% CI 0.497-0.586], 0.559 [95% CI 0.504-0.621]). Pastoral area was associated with shorter diagnostic delay among the group-1 with 30 days (aOR, 0.889 [95%CI 0.831-0.951]) and the group-3 with 90 days(aOR, 0.806 [95%CI 0.727-0.893]). Stratified analysis showed that older age was associated with increased risk of longer delay in both genders(P<0.05), The older age group-to-youth group OR increased along with increased delay time(P for trend<0.001). And the pastoral area was associated with shorter delay in males(P< 0.05). Delays exists in the diagnosis of human brucellosis. Regard with human brucellosis, high attention should be paid to the risk factors of diagnostic delay such as older population, non-herdsman, non-pastoral area, and non-disease prevention and control agencies. Effective measures should be taken to shorten the diagnostic duration, aiming to achieve early detection, early diagnosis, and early treatment, and to reduce the risk of chronicity, complications and economic burden in human brucellosis.